Control of refractive index by annealing to achieve high figure of merit for TiO2/Ag/TiO2 multilayer films. Issue 12 (September 2016) - Kim, Jae-Ho; Kim, Dae-Hyun; Kim, Sun-Kyung; Bae, Dukkyu; Yoo, Young-Zo; Seong, Tae-Yeon
Abstract: We modified the refractive index ( n ) of TiO2 by annealing at various temperatures to obtain a high figure of merit (FOM) for TiO2 /Ag/TiO2 (45 nm/17 nm/45 nm) multilayer films deposited on glass substrates. Unlike the as-deposited and 300 °C-annealed TiO2 films, the 600 °C-annealed sample was crystallized in the anatase phase. The as-deposited TiO2 /Ag/as-deposited TiO2 multilayer film exhibited a transmittance of 94.6% at 550 nm, whereas that of the as-deposited TiO2 /Ag/600 °C-annealed TiO2 (lower) multilayer film was 96.6%. At 550 nm, n increased from 2.293 to 2.336 with increasing temperature. The carrier concentration, mobility, and sheet resistance varied with increasing annealing temperature. The samples exhibited smooth surfaces with a root-mean-square roughness of 0.37–1.09 nm. The 600 °C-annealed multilayer yielded the highest Haacke's FOM of 193.9×10 −3  Ω −1 .